Kualitas Jasa dan Hubungannya dengan Loyalitas Serta Komitmen Konsumen: Studi pada Pelanggan Salon Kecantikan - Farida Jasfar (Jurnal Siasat Bisnis, 2005)
The purpose of the study was to determine whether consumer loyalty mediates between service quality and consumer commitment in the beauty salon industry. It was also to determine whether these relationships difference between beauty salon in shopping centers and beauty salon in community residences.A theoretical framework was developed to test the positive relationships among the study constructs. The study utilized service quality developed by Fullerton and Taylor (2000); Parasuraman, Zeithaml and Berry (1994), consumer loyalty developed by Unclesand Laurent (1997); Fullerton and Taylor (2000), and consumer commitment developed by Morgan and Hunt (1994); Fullerton and Taylor (2000).The degree of customer loyalty, commitment, and service quality was measured by using the Likert scale based on 238 valid questionnaire respondents (59,5% from 400 dispersed questionnaires).An analysis of the data revealed two major findings: First; there is a positive relationship between service quality and consumer loyalty, affective commitment, and continuum commitment. Second; consumer loyalty is the mediating variable of the relationship between service quality and consumer commitment both in beauty salons in shopping centers and beauty salons located in community residences. The results of this study have important implications for practicing managers of beauty salons and their understanding of the relationship between service quality, consumer loyalty and consumer commitment.Key words: services quality, loyalty, and commitment.